ANALISIS IMPLEMENTASI BUDAYA KERJA SEBAGAI UPAYA MENINGKATKAN OPERASI JASA DAN KUALITAS KARYAWAN DI UD. BOEROQ MOTOR CYCLE (BMC) KARANGASEM JENU TUBAN - Nurul Badriyah; Edy Susanto; Rismaya Nikmatul Hida Saskia Putri (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This research is motivated by the importance of the role of human resources (HR) in achieving company goals. A good work culture is believed to improve the quality of HR and achieve company targets. The purpose of this study is to describe and analyze the role of work culture in improving service operations and employee quality at UD. Boeroq Motor Cycle (BMC) Karangasem-Jenu-Tuban. This study uses a descriptive qualitative approach with a phenomenological research type. The results of the study indicate that work culture plays a role as a set of knowledge that is the foundation of a person's life. Work culture also plays a role in improving service operation management through indicators such as quality standards and production design according to consumer demand. The implementation of work culture at UD. BMC is able to create positive values ​​that can be applied and developed into company regulations. This study is expected to encourage employees to improve service operations and self-quality, so that the company's vision and mission are achieved. The implication of this study is the importance of implementing a good work culture to improve employee performance and achieve company goals.